Preliminary Study of Nondestructive Testing of the Polymer Cutoff Wall Based on Vibration Theory - Shu Zhang; Binghan Xue; Jing Wang; Jianglin Gao; Chaojie Wang; Wenzhong Li (Advances in Materials Science and Engineering)
The polymer cutoff wall offers the benefits of causing little disturbance to the dam body, being convenient and economical to construct and practical to use, and possessing good resistance to seismic shocks and cracks. It has been widely used to prevent seepage and to reinforce dikes and dams. However, the polymer cutoff wall is a concealed underground structure, and nondestructive testing methods to ensure its integrity are not yet mature. This paper describes a modal analysis of polymer cutoff wall models with different damage scenarios to investigate the feasibility of nondestructive testing of the polymer cutoff wall based on vibration theory. The dynamic characteristics of the first three natural frequencies of the wall and their mode shapes show that horizontal direction damage and centrally located partial damage have a noticeable impact on the dynamic characteristics of the wall, indicating that nondestructive testing based on vibration theory is useful to test for horizontal damage and moderate damage located centrally in the wall.